Demographics in Children Presenting With Acute Neurologic Deficits Concerning for Stroke: An Evaluation of the Stroke Alert Process. (April 2022) - Barkley, Tiffany; Khalid, Roha; Sharma, Mukta; Sherman, Ashley; Flint, Jennifer
Objective: To assess the demographics and clinical characteristics of children presenting with acute neurologic symptoms concerning for stroke.Background: Stroke leads to significant morbidity in the pediatric population. Stroke protocols were created as a means to help identify and triage these children. Despite implementation of these protocols, there have been few population-based studies evaluating the demographics and clinical features of children presenting with acute strokelike symptoms.Methods: A retrospective chart review of patients for whom the stroke alert process was activated from September 2016 through August 2018 at Children's Mercy Hospital.Results: There were a total of 61 activations. Acute ischemic stroke or transient ischemic attack comprised 18% and was the second leading diagnoses after seizure with postictal (Todd) paralysis (20%). Two activations were candidates for mechanical thrombectomy, and none received tissue plasminogen activator (tPA). Children with acute ischemic stroke / transient ischemic attack were likely to be younger in age (median 4 years, interquartile range [IQR] 3-9) compared to those with nonischemic stroke diagnoses (median 12.5 years, IQR 7-15.3) ( P  = .010). The anatomical location of acute ischemic stroke was widespread, including both anterior and posterior circulations. Past medical history, family history, racial demographics, sex, and initial presenting symptoms were not predictive of the diagnosis of acute ischemic stroke / transient ischemic attack. 38% of activations with diagnoses other than transient ischemic attack / acute ischemic stroke required urgent treatment, with 16% requiring intensive care unit admission.Conclusion: Acute ischemic stroke / transient ischemic attack comprised nearly one-fifth of all pediatric stroke activations, highlighting the importance of developing protocols for early recognition and evaluation of children who present with symptoms concerning for stroke.